2010
DOI: 10.1111/j.1540-8167.2009.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Electrophysiology of Complex Fractionated Atrial Electrograms: Insight from Noncontact Unipolar Electrograms

Abstract: The bipolar repetitive and continuous fractionated CFAEs represented different activation patterns. The former was associated with an S wave predominant unipolar morphology which may represent an important focus for maintaining AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
(87 reference statements)
3
17
0
Order By: Relevance
“…Limited data exist as to the clinical relevance of CEA sites, but 1 human study did suggest that CEA sites may be more associated with sites of passive atrial activation compared with CFAE sites, demonstrating short CLs. 26 The better outcome in group I (the generalized arm), and the increased incidence of repeat procedures in group II (the selective arm), would certainly support this hypothesis. Interestingly, some studies have suggested that more extensive CFAE ablation could increase the risk of recurrent AT or AFL.…”
Section: Selective Versus Generalized Cfae Regionssupporting
confidence: 55%
“…Limited data exist as to the clinical relevance of CEA sites, but 1 human study did suggest that CEA sites may be more associated with sites of passive atrial activation compared with CFAE sites, demonstrating short CLs. 26 The better outcome in group I (the generalized arm), and the increased incidence of repeat procedures in group II (the selective arm), would certainly support this hypothesis. Interestingly, some studies have suggested that more extensive CFAE ablation could increase the risk of recurrent AT or AFL.…”
Section: Selective Versus Generalized Cfae Regionssupporting
confidence: 55%
“…In AF, CFAE sites tend to have lower mean voltage than non-CFAE sites [13,22]. Furthermore, CFAEs with shorter cycle lengths (≤120 ms) or continuous electrical activity are associated with lower mean voltages than CFAEs with longer cycle lengths (Ͼ120 ms) [13,22]. These observations hold true when CFAE amplitudes are measured in terms of bipolar peak-to-peak voltage [13,20,22], unipolar peak negative voltage [22] and monophasic action potential voltage [20].…”
Section: Voltage Mapssupporting
confidence: 53%
“…While the initial report of CFAE ablation targeted only low voltage signals (≤0.15 mV) [5], subsequent reports have used numerous or even no voltage criteria. In AF, CFAE sites tend to have lower mean voltage than non-CFAE sites [13,22]. Furthermore, CFAEs with shorter cycle lengths (≤120 ms) or continuous electrical activity are associated with lower mean voltages than CFAEs with longer cycle lengths (Ͼ120 ms) [13,22].…”
Section: Voltage Mapsmentioning
confidence: 99%
“…This modeling study of heterogenous tissue demonstrates that 1) structural heterogeneity in the border zone between well-coupled and poorly coupled tissue may actively facilitate the formation of reentrant circuits and 2) electrogram asymmetry, particularly a single negative deflection, combined with small, fractionated signals may be reliable indicator for locating the dynamic microscopic sites of wavefront breakthrough that lead to microreentry. This "S wave" electrogram morphology (negative deflection) has been observed clinically at recording sites in the arrhythmogenic pulmonary veins and at a site of ectopic activation and breakthrough (14,25). In a recent three-dimensional computational study (39) of a human atrial model with fiber orientation, electrode recordings using surface electrodes have shown negative deflections at the macroscopic level near sites of ectopic foci.…”
Section: Discussionmentioning
confidence: 78%